Analisis Perbandingan Metode Peramalan Single Exponential Smoothing dan Double Exponential Smoothing pada Harga Pembukaan Harian XAU/IDR - Putra, Rachmad Maulana (Institut Teknologi Adhi Tama Surabaya, 2023)
The widespread availability of information in the digital age has made gold investment more accessible to a wider audience. In the Forex market, the world's largest foreign exchange market, gold is traded under the code XAU and is considered a major, stable commodity. Despite the ease of gold investment, fluctuating gold prices pose a significant challenge, making price prediction difficult. This research employs Single Exponential Smoothing and Double Exponential Smoothing methods to determine the most optimal forecasting approach based on the lowest Mean Absolute Percentage Error (MAPE) and Root Mean Square Error (RMSE) values. The study also utilizes Solver for parameter optimization to achieve the most optimal MAPE and RMSE values. Findings indicate that Single Exponential Smoothing is more optimal for gold price prediction, with a MAPE value of 0.63% and an RMSE value of 2518.38604